Transition‐Metal‐Free Cleavage of CO - Devillard, Marc; de Bruin, Bas; Siegler, Maxime A.; van der Vlugt, J. I. (Chemistry : a European journal, 2017)
Tertiary silane 1H, 2‐[(diphenylsilyl)methyl]‐6‐methylpyridine, reacts with tris(pentafluorophenyl)borane (BCF) to form the intramolecular pyridine‐stabilized silylium 1+‐HBCF. The corresponding 2‐[(diphenylsilyl)methyl]pyridine, lacking the methyl‐group on the pyridine ring, forms classic N(py)→B adduct 2H‐BCF featuring an intact silane Si−H fragment. Complex 1+‐HBCF promotes cleavage of the C≡O triple bond in carbon monoxide with double C−Csp2 bond formation, leading to complex 3 featuring a B‐(diarylmethyl)‐B‐aryl‐boryloxysilane fragment. Reaction with pinacol generates bis(pentafluorophenyl)methane 4 as isolable product, proving the transition‐metal‐free deoxygenation of carbon monoxide by this main‐group system. Experimental data and DFT calculations support the existence of an equilibrium between the silylium–hydroborate ion pair and the silane–borane mixture that is responsible for the observed reactivity. Que Si, que CO: The transition‐metal‐free complete deoxygenation of CO is achieved using a combination of the tertiary silane 2‐[(diphenylsilyl)methyl]‐6‐methylpyridine (1H) and B(C6F5)3 (BCF), which generates the intramolecular pyridine‐stabilized silylium 1+‐HBCF. In the process of CO activation, one new C−H and two new C−Csp2 bonds are formed. Hydrolysis with pinacol gives H2C(C6F5)2 as isolable product. DFT has provided insight in the plausible pathway for this remarkable transformation.